Vital and non-vital bleaching of discoloured upper central incisors: a case report - Mustaffa, Musliana (Malaysian Endodontic Society, 2020)
A 30-year-old female patient was referred to the Charles Clifford Dental Hospital (CCDH) for the management of discoloured upper central incisors. On presentation, patient complained of discoloured upper front teeth with no pain or discomfort associated with the teeth. Patient had history of trauma when she was 10 years old, had root canal treatment done on tooth 21 due to the trauma and claimed that the teeth were gradually discoloured until became noticeable. The diagnosis was intrinsic tooth discolouration, root canal treated of tooth 21 with asymptomatic periapical periodontitis and sclerosed canal associated with tooth 11. Non-surgical root canal retreatment was carried out on tooth 21 followed by vital and non-vital bleaching of tooth 11 and 21 respectively.